Ранние комплексные общества в древней истории Восточной Европы - Массон, В.М. (Археологія, 1995)
В статье на основе археологического материала дается всесторонняя характеристика ранних комплексных обществ Восточной Европы, рассматриваются пути их развития, наличие связей с традициями других цивилизаций. Ранні комплексні суспільства характеризуються: ієрархізацією організаційних структур; ускладненням структур у соціальній, політичній та економічній сферах, де остання помітно відрізняється від народження до певної страти. Збільшується значення лідерів в інтеграції суспільства. Нові організаційні можливості дозволяли шляхом концентрації зусиль отримати ефект, особливо помітний у будівельній діяльності. Разом з тим, розпливчастість соціальних страт, ще недостатньо закріплених майновим статусом, характерним для перших цивілізацій та держав робили ранні комплексні суспільства нестійкими утвореннями. У їхніх долях діалектично перепліталися злети й падіння, консолідація та дезінтеграція. Можна говорити про два основні шляхи розвитку ранніх комплексних суспільств — урбаністичний та неурбаністичний. Перший є типовим для Близького Сходу. Неурбаністичний шлях розвитку представлений в Євразії принаймні двома варіантами. Перший — це неурбаністичний розвиток ранньоземлеробських суспільств Південно-Східної та Центральної Європи. Іншим варіантом є культури степової бронзи Євразії, де скотарський сектор економіки відігравав особливу роль. Трипільське суспільство Молдови й України можна розглядати як один з проявів неурбанічного шляху розвитку балканського виду. Нові відкриття гробниць майкопської культури (III тис. до н. е.), де нові дослідження призвели до відкриття складних укріплених поселень й багатих поховань воїнів-колісничих. Цікавим є наявність у подібних суспільствах Поволжя, Південного Уралу та Зауралля елементів, пов'язаних з традиціями мікенської цивілізації. Early complex societies features: hierarchization of the basic structures; increasing complexity of social, political and economic patterns, essentially distinct from the primitive autarchy. The emerging social hierarchy manifested itself, in an individual initially belonging to a certain social stratum, in the increasing importance of central power (and of a personified leader-chief) and in social integration. The new organizational potentialities, which enabled one to achieve considerable gains by means of concentrated efforts, were particularly effective in monumental architecture. At the same time, the vagueness of the social strata was not definitely strengthened by property ranking, which was typical of early civilizations and states, resulting in the instability of early complex societies. The historic destinies of these societies dialectically combined the rise and fall, consolidation and disintegration.
One may distinguish: 1) urban and 2) non-urban development in early complex societies; the first being typical of the Near East. In the second line of development, in Eurasia, one may distinguish two variants: the non-urban development of early agricultural structures in Southeastern and Central Europe; and non-urban development of the Bronze Age cultures of the Eurasian steppes, essentially based on stock- breeding.
The Tripoly society in Ukraine and Moldova is seen as a variant of the Balkan-type development.
The newly discovered burial assemblages of the Maikop culture (3rd millennium BC) indicate the institutionalized military power of local leaders, which enabled them to carry out large-scale constructions.
Military functions were particulary important in early complex societies of the South Urals and in Northern Kazakhstan (middle of the 2nd millennium BC), where recent investigations have brought to light complicated fortified settlements and the rich burials warriors.
It is noteworthy that societies of such type found in the Volga, South Urals and Trans-Urals areas featured the occurrence of elements related to the Mycenean civilization.